2018
DOI: 10.1002/lary.27132
|View full text |Cite
|
Sign up to set email alerts
|

An internally validated prognostic model for success in revision stapes surgery for otosclerosis

Abstract: 2b. Laryngoscope, 128:2390-2396, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 39 publications
2
9
0
1
Order By: Relevance
“…A recently published multivariable prediction model pointed out that type of the previously performed procedure, primary cause of failure, and type of the prosthesis placed during revision surgery are associated with postoperative success in otosclerosis patients undergoing revision stapes surgery. 26 In our study, previous type of procedure and primary cause of failure were not associated with success. The type of the prosthesis placed during revision surgery did not vary all that much in our study population; 61 cases received an incus-to-oval-window prosthesis, and only 5 cases received a malleus-to-oval-window prosthesis.…”
Section: Discussionmentioning
confidence: 41%
“…A recently published multivariable prediction model pointed out that type of the previously performed procedure, primary cause of failure, and type of the prosthesis placed during revision surgery are associated with postoperative success in otosclerosis patients undergoing revision stapes surgery. 26 In our study, previous type of procedure and primary cause of failure were not associated with success. The type of the prosthesis placed during revision surgery did not vary all that much in our study population; 61 cases received an incus-to-oval-window prosthesis, and only 5 cases received a malleus-to-oval-window prosthesis.…”
Section: Discussionmentioning
confidence: 41%
“…In the study, the success rate of surgery was reported 95.7%. In the same study, the tympanic perforation after stapedotomy was reported 1.1% [12]. In the present study, 91.4% of patients had hearing improvement as a decrease above 15 db in air bone gap, but the difference in surgery by attending physicians and fellows was not significant, and their complications were not significantly different.…”
Section: Discussionsupporting
confidence: 42%
“…Importantly, success in revision stapes surgery is correlated with an accurate diagnosis of the cause of failure . For example, the extent of incus necrosis dictates repair options and ultimately clinical outcomes .…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have shown that the most common causes of failure after primary stapes surgery include prosthesis dislocation, short or long prosthesis, incus erosion or dislocation, perilymphatic fistula, and ankylosis of the lateral ossicular chain . The success of revision stapes surgery relies on intraoperative identification of the cause for initial surgical failure because a lack of diagnosis has been correlated with negative outcomes . Consequently, adequate visualization and evaluation of the ossicular chain and oval window are essential to accurately diagnose and treat the cause of failure.…”
Section: Introductionmentioning
confidence: 99%